(untitled) (Journal of Pathology of Nepal, 2014)
Primary soft tissue tumors of the penis, such as leiomyomas, are very rare. To the best of our knowledge, less than ten cases have been reported till date. The lesion gradually increases in size and can mimic a malignant lesion. Excisional biopsy and histopathological examination can provide the diagnosis as well as cure, both physical and psychological. We report a case of a penile shaft leiomyoma in a 49 year old male. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11598 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 680-681